THE CONCEPT OF TRANSFER PRICING SYSTEM IN RUSSIAN FEDERATION - Alexey S. Besfamilnyy (Статистика и экономика, 2016)
The article presents the author's denition of transfer prices and transfer pricing based on the analysis of the current legislation in Russia as well as on current economic practice. Considered state regulation of transfer pricing for the purpose of harmonization of relationship between government and business. Given the denition of the transfer pricing system in Russian Federation and the description of its main parts and connections between them, necessary for effective functioning.